PERAN PEMERINTAH DESA DALAM MENINGKATKAN PRODUKTIVITAS HASIL PERKEBUNAN DI DESA ERA BARU KECAMATAN TELLULIMPOE - Amir, Muh.; Jusniaty, Jusniaty; Salman, Salman; Abdillah, Ashar; Fakhruddin, Faiz (Gapenas Publisher, 2025)
This study aims to analyze the role of the New Era Village Government in increasing plantation productivity and identifying the obstacles faced in its implementation. New Era Village, Tellulimpoe District, is an area with considerable plantation potential, with main commodities such as cocoa, cloves, rubber, and coconut. Although there has been an increase in commodity prices from 2022 to 2024, the increase in productivity has not been proportional to this increase. This study uses a qualitative approach with a descriptive method. Data were obtained through in-depth interviews, field observations, and documentation, involving key informants such as village government officials, farmer groups, agricultural extension workers, and community leaders. This research was conducted in Era Baru Village, Tellulimpoe District, Sinjai Regency. The results of this study show that the role of the village government in increasing plantation yields, based on the following indicators, is as follows: (1) The role of the village government as a policy implementer has been carried out by providing fertilizer and seeds to farmer groups. (2) The role of the village government as a program implementer has been carried out by increasing the capacity of farmers through training on Biological Control Agents and the Production of Bokashi Compost. (3) The role of the village government as a mentor has been carried out by mentoring 29 Farmer Groups and 1 Joint Farmer Group. Thus, it can be concluded that the village government and farmer groups must